Thick film, acoustic emission sensors for embedded structural health monitoring systems - Pickwell, A. J.; Dorey, Robert A.; Mba, David (Cranfield University, 2010)
Structural heath monitoring of engineering structures is of growing interest due to increasedcomplexity of such structures and the ability to schedule maintenance when it is needed thuspreventing unnecessary work or preventing failure. One such method for monitoring the structuralhealth of large scale structures is through the detection of Acoustic Emissions (AE). A novel thickfilm Acoustic Emission sensor is presented. Piezoelectric thick film AE sensors were fabricated bycreating and pattering lead zirconate titanate (PZT) thick films using a powder/sol composite inkdeposition technique in conjunction with mechanical patterning of the subsequent films. The resultantAE sensors exhibit a response comparable to commercially available AE sensors. Comparative resultsbetween the thick film and commercial sensors will be reviewed and discussed.